Mediating Role of Employee Retention on the Relationship between talent management practices and SMEs Performance in Yobe State, Nigeria. - Ahmadu Isah, Ahmadu Isah; Aminu Ibrahim, Dr. Murtala Aminu Ibrahim (Research in Management of Technology and Business, 2024)
AbstractSmall and medium enterprises (SMEs) has been recognized as one of the major factors that enhances the economic performance of any Country. Particularly, SMEs contribute to the economic growth and development of developing countries like Nigeria. However, as a developing Country, SMEs in Nigeria faces a lot of challenges which include poor performance. Talent management practices (TMP) can be used to overcome some of these challenges. Similarly, past studies show that talent management practices has significant influence on SMEs performance. However, the role of employee retention in understanding the mechanism through which TMP dimensions are related to SMEs performance is ignored. Therefore, this paper proposes that employee retention as a mediating variable may further help explain the relationship between TMP and SMEs performance